Investigations on metallurgical and mechanical properties of CO2 laser beam welded Alloy 825. (3rd April 2017) - Arivarasu, M.; Roshith, P.; Padmanaban, R.; Thirumalini, S.; Phani Prabhakar, K. V.; Padmanabham, G.
ABSTRACT: In the research work, an attempt is made to join nickel-based alloy 825 by employing CO2 laser beam welding. Successful full penetration weld joint of a 5 mm thick plate is achieved with a very low heat input of 120 J-mm −1 . Narrow weld bead width of 0.6 mm at the root and 1.6 mm at the cap is observed fusion zone; the interface and base metal microstructures have been examined using both optical and scanning electron microscopic techniques to understand the microstructural changes which have occurred due to laser welding. A range of tests of Vickers micro hardness, tensile and impact tests had been performed on the weldment to ascertain the mechanical properties of the joint. Tensile failure at the base metal and a 180° root bend test conducted on the weldment ascertain the soundness of the weld joint produced. An attempt is made to correlate the microstructure and mechanical properties of the weldment. Intermetallics TiN and Al4 C3 observed in the SEM\EDS analysis at the fusion zone are found to have improved the weld metal strength and hardness.